Sistem Pakar Mendeteksi Penyakit Ikan Arwana Asia Menggunakan Metode Naïve Bayes - Efendi, Alvian Nur; Triayudi, Agung; Winarsih, Winarsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Asian Arowana fish are freshwater fish that are spread across Southeast Asia. Many Indonesian people maintain Arowana fish because of its beauty and also has a high enough price. But in the process of cultivation, the Asian Arowana Fish can be attacked by more than one disease that can threaten the survival of the Arowana fish. With the rapid advancement of technology that is taking place and based on these problems, the author implements an Expert System to detect what diseases attack these fish with symptoms and data obtained from experts so that we know what steps must be taken for the prevention and sustainability of Arowana fish cultivation. The method used is the Naïve Bayes Method, which is a probability statistical method that can detect whether a fish is exposed to a disease with pre-existing web-based odds.
Keywords: Expert System; Naïve Bayes; Asian Arowana Fish